PECULIARITIES OF DETERMINATION OF DECISION ABOUT TERMINATION OF PREGNANCY IN WOMEN OF DIFFERENT AGE GROUPS - V. Yakuhina (Вестник университета)
The problem of a decision making in the situation of a complicated choice, a particular manifestation of which is unwanted, unplanned pregnancy is a particular case, retains its popularity in various elds of psychology. It is becoming extremely relevant due to the decline in the birth rate in our country. The purpose of this article is to identify the peculiarities of determination of the decision to terminate such pregnancy in women of dierent age groups, which will allow doctors and psychologists in the system of psychological counseling to make adjustments in working with them.